(untitled) (Annual of the Faculty of Philosophy in Skopje, 2022)
This paper aims to show how the Greek Great Idea came about, as well as the impact it had on Greek society, science, foreign policy, as well as on the building up of nationalism. The full text of the speech made by Ioannis Kolettis on January 14, 1844 is provided in one section of this paper. It is our belief that it should be published for the sake of the past, the present, and the future. Kolettis, originally an Aromanian from Epirus, then a part of the Ottoman state, was a highly influential politician in independent Greece. He participated in the building of the institutions of the new state. His speech was allegedly not meant to inflame Greek nationalism and reinforce aspirations for territorial expansion of the first independent and Orthodox state in the Balkans. What Kolettis wanted to get across was that all those who participated in the uprising of 1821, regardless of whether they were born in the territory of the new state or in the Ottoman Empire, had the right to Greek citizenship. However, the words he used in the speech, especially the term “The Great Idea” (Μεγάλη ιδέα), led to a flare-up of nationalism and a change in the views of the past, especially on the issue of ancient Macedonia and Byzantium, as well as to a public display of territorial claims to the neighbouring Ottoman state. His speech became a guide for the future foreign and national policy of the Kingdom of Greece.